Impact of Sustainability Reporting on Firm Value with Audit Quality as Moderator: Coal Companies - Butar Butar, Dea Tiara Moonalisa; Itan, Iskandar (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study examines the impact of sustainability reporting on firm value in coal mining companies in Indonesia and investigates the moderating role of audit quality in this relationship. Rooted in agency theory, this study addresses the issue of information asymmetry between managers and shareholders, especially in environmentally sensitive industries. This study uses a quantitative approach using sustainability reporting as the independent variable, firm value as the dependent variable, and audit quality as the moderator variable. The study classifies sustainability reporting as non-experimental with time series and cross-sectional data classification. The research sample consists of 11 coal mining companies listed on the Indonesia Stock Exchange for the years 2020-2023. Using panel data from 2020-2023 and applying regression analysis, this study finds that sustainability reporting significantly increases firm value. In addition, audit quality strengthens this relationship, indicating that credible audits increase stakeholders' trust in disclosed Environmental, Social, and Governance information. These findings highlight that transparent reporting and reliable assurance mechanisms play an important role in improving firm valuation. This article contributes to the literature by emphasizing the interaction between non-financial disclosure and corporate monitoring in emerging markets.